Analisis Kebijakan Merdeka Belajar: Transformasi Sistem Pendidikan Indonesia dalam Perspektif Keadilan dan Pemerataan Akses - Astuti, Lidya Puji; Sumarti, Elis; Nurhayati, Nurhayati; Huggannah, Huggannah; Musfirowati, Musfirowati; Meiyanti, Mila; Dariana, Rani; Effendi, Darwin; Akbariansyah, Akbariansyah (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2026)
This study aims to analyze the direction and substance of the Merdeka Belajar policy, identify its implementation challenges from the perspective of justice and equal access to education, evaluate its contribution to the equalization of educational quality, particularly in 3T regions (frontier, outermost, and disadvantaged areas), and formulate evidence-based strategic recommendations. This research employed a qualitative approach using the library research method. Data were collected through documentation studies of official policy documents, scientific journals, and relevant institutional reports, and were analyzed through the stages of data reduction, data presentation, and conclusion drawing using source triangulation to ensure data validity. The findings indicate that the Merdeka Belajar policy represents a paradigmatic transformation in education from a teacher-centered approach toward student-centered learning, implemented through the Merdeka Curriculum, National Assessment, and the Guru Penggerak program. However, the implementation of the policy still faces several structural challenges, including disparities in digital infrastructure, unequal teacher capacity, and weak coordination between central and regional governments. These conditions have hindered the equitable distribution of policy benefits, particularly in 3T regions, which remain the most vulnerable areas. The study concludes that achieving substantive educational justice requires policy differentiation based on regional typology, strengthening adaptive and contextual teacher training systems, accelerating digital infrastructure development, and reinforcing multi-stakeholder educational governance involving schools, universities, local governments, and industry sectors.